2010
DOI: 10.1159/000321139
|View full text |Cite
|
Sign up to set email alerts
|

Could Alkali Production Be Considered an Approach for Caries Control?

Abstract: This study investigated the relationship of arginine deiminase (ADS) and urease activities with dental caries through a case-control study. ADS and urease activities were measured in dental smooth-surface supragingival plaque and whole saliva samples from 93 subjects, who were in three different groups: caries-free (n = 31), caries-active (n = 30), and caries-experienced (n = 32). ADS activity was measured by quantification of the ammonia generated from the incubation of plaque and saliva samples in a mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 65 publications
2
47
1
4
Order By: Relevance
“…Firstly, in situ ammonia production from salivary arginine via the arginine deiminase system in dental plaque is positively associated with reduced caries experience [Nascimento et al, 2009;Gordan et al, 2010], indicating the importance of ammonia production in caries prevention. Further, it has been shown that fluoride-free toothpaste containing 1.5% arginine significantly increased arginine deiminase system activity in caries-active individuals, indicating that exogenous arginine can reduce caries risk by increasing arginine deiminase system activity [Nascimento et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in situ ammonia production from salivary arginine via the arginine deiminase system in dental plaque is positively associated with reduced caries experience [Nascimento et al, 2009;Gordan et al, 2010], indicating the importance of ammonia production in caries prevention. Further, it has been shown that fluoride-free toothpaste containing 1.5% arginine significantly increased arginine deiminase system activity in caries-active individuals, indicating that exogenous arginine can reduce caries risk by increasing arginine deiminase system activity [Nascimento et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Sugar substitutes instead of dietary sugar are a better option as these cannot be directly broken down by bacteria and this in turn reduces the acid production. Supplements like arginine or urea can be used that are metabolized by plaque bacteria to alkali which in turn increases the pH which inhibits the acid producers ultimately reducing the acid production [47,48]. In silico approaches have been used to validate the significance of pH based on the degree of acid buffering capacity.…”
Section: Possible Treatmentmentioning
confidence: 99%
“…9 Obtención de saliva: Se colectaron 5 mL de saliva no estimulada, en la mañana, en un tubo de plástico estéril de 15 mL, mantenido a 4 °C hasta su traslado al laboratorio de química (Facultad de Odontología, Universidad de Chile). La saliva se transfirió a tubos de centrífuga de 1,5 mL para su posterior análisis en el laboratorio de Microbiología (Facultad de Odontología, Universidad de Chile).…”
Section: Obtención De Muestras Y Procedimientounclassified
“…9 Saliva collection: 5 mL of non-stimulated saliva were collected in the morning in a 15 mL sterile plastic tube, which was maintained at 4 °C until brought to the Chemistry Laboratory (School of Dentistry, Universidad de Chile). The saliva was transferred to 1.5 mL centrifuge tubes for further analysis in the Microbiology Laboratory (School of Dentistry, Universidad de Chile).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation